Sediments of MIS 5e age suggested by new OSL dates from the Skilvika section, west Svalbard. Issue 1 (1st January 2018) - Alexanderson, Helena; Landvik, Jon Y.
ABSTRACT: The sediment succession at Skilvika, west Svalbard, represents one of the key stratigraphic records of the Late Quaternary palaeoenvironments and glaciation history of the Svalbard/Barents Sea area. A formation of raised marine sediments, interfingering with and capped by glacial deposits of local origin, have previously been assumed to be of an Early Weichselian age, likely marine isotope stage (MIS) 5c. Here we present a new series of optically stimulated luminescence (OSL) ages that suggest the events took place in MIS 5e. This advocates a revision of the correlation with other key stratigraphic sites on Svalbard.